Cardio Policy Optimiser - Lopes, Henrique (2024)
Lopes, H., Baptista-Leite, R., Coelho, P. S., Mendes, J. M., Castro, M., & Diogo, J. R. (2024). Cardio Policy Optimiser: an integrated public health approach to enhancing cardiovascular health [abstract]. European Journal of Public Health, 34(Supplement 3), 456-457. https://doi.org/10.1093/eurpub/ckae144.1171